Changes in sexual desires and behaviours of people living with HIV after initiation of ART: Implications for HIV prevention and health promotion - Wamoyi, Joyce; Mbonye, Martin; Seeley, Janet; Birungi, Josephine; Jaffar, Shabbar (BMC Public Health, 2011)
Abstract Background: As immune compromised HIV sero-positive people regain health after initiating antiretroviral treatment (ART), they may seek a return to an active ‘normal’ life, including sexual activity. The aim of the paper is to explore the changing sexual desires and behaviour of people on ART in Uganda over a 30 month period. Methods: This study employed longitudinal qualitative interviews with forty people starting ART. The participants received their ART, adherence education and counselling support from The AIDS Support Organisation (TASO). The participants were selected sequentially as they started ART, stratified by sex, ART delivery mode (clinic or home- based) and HIV progression stage (early or advanced) and interviewed at enrolment, 3, 6, 18 and 30 months of their ART use. Results: Sexual desire changed over time with many reporting diminished desire at 3 and 6 months on ART compared to 18 and 30 months of use. The reasons for remaining abstinent included fear of superinfection or infecting others, fear that engaging in sex would awaken the virus and weaken them and a desire to adhere to the counsellors’ health advice to remain abstinent. The motivations for resumption of sexual activity were: for companionship, to obtain material support, social norms around marriage, desire to bear children as well as to satisfy sexual desires. The challenges for most of the participants were using condoms consistently and finding a suitable sexual partner (preferably someone with a similar HIV serostatus) who could agree to have a sexual relationship with them and provide for their material needs. Conclusions: These findings point to the importance of tailoring counselling messages to the changing realities of the ART users’ cultural expectations around child bearing, marriage and sexual desire. People taking ART require support so they feel comfortable to disclose their HIV status to sexual partners.
Keywords: Sexual desire; ART; HIV; Longitudinal; Sexual behaviour